ANALYSIS OF STUDENTS’ MATTER ABILITY IN SPEAKING FOR DEBATE AT FOURTH SEMESTER IN MUHAMMADIYAH UNIVERSITY OF BENGKULU - Acacia Agnes Dwita Ariesy; Ririn Putri Ananda (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Matter in debate is the content of debate. Matter is seen as the main thing in conveying the arguments. However, the students often do not attentive on their matter in which reduce the quality of their debate performance. The aim of this study is to identify how students’ matter ability in speaking for debate at fourth semester in Muhamadiyah University of Bengkulu. The data were taken from three steps, namely ; exercise, middle test, and final examination and were analyzed on elements of matter following Simon Queen (2005). This research used a descriptive method. The subjects of this research were 34 students at fourth semester who attended the course as speaking for debate at the English Study Program, Muhammadiyah University Of Bengkulu. The result showed that the students is low criteria with a percentage of 27%. Not all the students have understood about use of the elements of matter. It is suggested that English students need to learn more about the elements of matter and evaluate their arguments. Keywords: Speaking, debate, matter ability